Lactic acid fermentation of pineapple wastes by lactobacillus delbrueckii [microfilm] - Abdullah Moch Busairi (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Doktor Falsafah) - Universiti Teknologi Malaysia, 2002